Significance of Tumor Size in Renal Cell Cancer with Perinephric Fat Infiltration: Is TNM Staging System Adequate for Predicting Prognosis? - Süer, Evren; Baltaci, Sümer; Burgu, Berk; Aydogdu, Özgü; Gögüs, Çagatay (Urology Journal, 2013)
PURPOSE: To evaluate the influence of perinephric fat infiltration and tumor size on survival of patients with renal cell carcinoma (RCC). MATERIALS AND METHODS: We have retrospectively reviewed the records of 338 consecutive patients with pT1-3aN0M0 RCC, including 275 pT1-2 and 63 pT3a tumors, who underwent open partial or radical nephrectomy between 1995 and 2008. Univariate and multivariate analyses were performed in order to evaluate the prognostic factors. RESULTS: Median follow-up period was 36.07 months. Receiver Operating Characteristic curve analysis determined the optimal tumor size cutoff value as 7 cm (Area Under the Curve: 0.65 ± 0.047; 95% Confidence Interval: 0.558 to 0.741). Perinephric fat invasion and Fuhrman grade were independent prognostic factors for disease-specific survival (DSS). In patients with tumor size >7 cm, perinephric fat invasion affected DSS significantly. Tumor size (according to the cutoff value of 7 cm) significantly affected DSS in patients with pT3a disease. According to the TNM 2002 staging system, perinephric fat invasion did not have any significant effect on DSS in patients with tumor size smaller than 4 cm, unlike tumor size of 4 to 7 cm and >7 cm. pT3a tumors larger than 7 cm demonstrated the worst prognosis compared to other groups. CONCLUSION: Perinephric fat invasion was demonstrated as a significant prognostic factor for RCC patients with tumor size >4 cm. Consequently, evaluation of pT3a patients should take tumor size into consideration for better prognostic analysis.